Monograph on trade channels : preserved tropical fruits and vegetables (including fruit juices) in the Federal Republic of Germany (ITC UNCTAD/GATT GenevaCH, 1987)
Market study on tropical fruit preparations in Germany FR. Gives comments and data on market segments (fruit juices, canned and bottled fruit and vegetables, dried fruit), notes on potential importers and distributors, distribution network, packaging and technical requirements, and gives recommendations for exporters in developing countries. Lists addresses.
IDS